Unveiling the Genetic Symphony: Harnessing CRISPR-Cas Genome Editing for Effective Insect Pest Management - J. Komal; H. R. Desai; Ipsita Samal; Andrea Mastinu; R. D. Patel; P. V. Dinesh Kumar; Prasanta Kumar Majhi; Deepak Kumar Mahanta; Tanmaya Kumar Bhoi (Plants, 2023)
Phytophagous insects pose a significant threat to global crop yield and food security. The need for increased agricultural output while reducing dependence on harmful synthetic insecticides necessitates the implementation of innovative methods. The utilization of CRISPR-Cas (Clustered regularly interspaced short palindromic repeats) technology to develop insect pest-resistant plants is believed to be a highly effective approach in reducing production expenses and enhancing the profitability of farms. Insect genome research provides vital insights into gene functions, allowing for a better knowledge of insect biology, adaptability, and the development of targeted pest management and disease prevention measures. The CRISPR-Cas gene editing technique has the capability to modify the DNA of insects, either to trigger a gene drive or to overcome their resistance to specific insecticides. The advancements in CRISPR technology and its various applications have shown potential in developing insect-resistant varieties of plants and other strategies for effective pest management through a sustainable approach. This could have significant consequences for ensuring food security. This approach involves using genome editing to create modified insects or crop plants. The article critically analyzed and discussed the potential and challenges associated with exploring and utilizing CRISPR-Cas technology for reducing insect pest pressure in crop plants.